Reciprocal interaction between vascular niche and sweat gland promotes sweat gland regeneration - Xingyu Yuan; Xianlan Duan; Enhejirigala; Zhao Li; Bin Yao; Wei Song; Yuzhen Wang; Yi Kong; Shijun Zhu; Fanliang Zhang; Liting Liang; Mengde Zhang; et al. (Bioactive Materials, 2023)
The incorporation of vasculature is known to be effective in tissue or organ functional regeneration. However, a vague understanding of the interaction between epidermal appendages and their vascular niches is a foremost obstacle to obtaining sweat gland (SG)-specific vasculature units. Here, we map their precise anatomical connections and report that the interplay between SG cells (SGCs) and the surrounding vascular niche is key for glandular development and homeostasis maintenance. To replicate this interplay in vitro, we used three-dimensional (3D) bioprinting to generate reproducible SGC spheroids from differentiated adipose-derived mesenchymal stem cells (ADSCs). With dermal microvascular endothelial cells (DMECs), sacrificial templates made from poly (ε-caprolactone) (PCL) were fabricated to pattern the vascular niche. This interplay model promoted physiologically relevant vascularized glandular morphogenesis in vitro and in vivo. We identified a reciprocal regulatory mechanism for promoting SGs regeneration via contact-independent cell communication and direct cell-cell interactions between SGs and the vasculature. We envision the successful use of our approach for vascularized organ regeneration in the near future.